A Broadband, Polarization Insensitive, Wide Incidence-Angle-Slotted Ring/Lumped Resistor-Based Metamaterial Absorber for K-u-Band Applications - AKŞİMŞEK, HÜSEYİN SİNAN (Istanbul University - Cerrahpaşa, 2021)
A broadband-slotted ring/lumped resistor-based metamaterial absorber (MA) is presented in this study for K-u-band microwave applications. Numerical results of the MA indicate that it can achieve a broadband absorption ratio of more than 85% in the frequency range of 12.4-17.6 GHz and has active polarization insensitivity and wide incidence-angle response over the entire operation band between 12.4-17.6 GHz. The designed MA is ultrathin around lambda/14.7 in terms of wavelength at its lowest operation frequency, corresponding to 1.7 mm. The proposed unit-cell structure of the MA is novel, consisting of a slotted ring with eight symmetrically-located lumped resistors, FR-4 material, and a metallic ground, which is compatible with low-cost PCB fabrication; therefore, the MA is suitable for practical microwave applications in the K-u-band.
Keywords: Terms—Broadband; Metamaterial Absorber; Ultrathin; K-u-Band